Grammar Me: The Development Of E-Learning Web System To Enhance Grammar Learning Experience Towards Education 4.0 - AZHAN, AIDA HUMAIRA; RAMLI, AZIZUL AZHAR (Applied Information Technology And Computer Science, 2023)
Grammar plays a significant role in English communication as it keeps sentences well-structured and meaningful. However, many students failed to communicate English fluently. As a result, English performance in Sijil Pelajaran Malaysia (SPM) had declined, and post-graduates could not secure a job. To minimize the problem of grammar inefficiency, a system has been developed. Therefore, virtual learning through the Grammar Me allows learning grammar through quizzes and interactive learning modules. The ADDIE-based method is used as a methodology to develop this application. The system is developed using Notepad++ with phpMyAdmin database to keep all data and Adobe Illustrator 2020 to illustrate graphics. The main language for this system is PHP, HTML, CSS and javascript. From questionnaire findings, almost every user was delighted with the system. Lastly, the system is suggested to have multiple choice of quizzes and find a good web hosting to ease the system process.